Effect of 8 weeks Aerobic Training and Artichoke Distillate on Lipid Profile and Liver Enzymes in Women with Non-Alcoholic Fatty Liver - Atefeh Jamshidpour; Vahid Tadibi; Nayebali Rezvani (Shahid Beheshti University, 2022)
Background and Purpose: Non-alcoholic fatty liver disease is the most common liver disease that is progressing and affects more than a quarter of the world's population. In this regard, researchers believe that exercise and herbal medicines with anti-lipid and antioxidant properties can be beneficial as supplementary therapy. Therefore, the aim of this study was to examine the effects of eight weeks aerobic training and artichoke distillate consumption on liver fat and serum levels of liver enzymes in women with non-alcoholic fatty liver.Materials and Methods: For this purpose, 24 obese or overweight volunteer women with non-alcoholic fatty liver with the mean age of 39.9±3.8 years, and mean weight of 75.4±12.1 kg, were randomly assigned into three groups of eight subjects: artichoke, aerobic, and control. Subjects in the aerobic group performed three sessions of aerobic exercises per week for eight weeks. The aerobic training program included 30 minutes of running with an intensity of 11 on the Borg scale rating of perceived exertion during the first week. Training duration increased to 45 minutes and the intensity increased to 13 from the fifth week of the aerobic training program, according to the principle of progressive overload. Subjects in the artichoke group received 180cc of the artichoke distillate per day (60cc after each meal). The control group performed no intervention during the study period. Blood sample and ultrasound sonography of the liver were performed 48 hours before and after the intervention to measure serum levels of Alanine Aminotransferase, Aspartate Aminotransferase, lipid profile (total cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein), and liver fat.Results: Results showed that liver fat levels were significantly decreased within the aerobic (P = 0.034) and the artichoke (P = 0.011) groups. However, there was no significant difference between the effectiveness of the aerobic training and artichoke distillate consumption (P = 0.393). Serum levels of Alanine Aminotransferase and Aspartate Aminotransferase had significant decrement within the aerobic group (P = 0.016 and P = 0.028, respectively). The levels of these enzymes had non-significant decrement within the artichoke group (P = 0.080 and P = 0.172, respectively), and significant increments within the control group (P = 0.024 and P = 0.008, respectively). There were no significant changes in the lipid profile within the groups.Conclusion: Performing three sessions of aerobic training with moderate intensity per week for eight weeks or consumption of 60cc artichoke distillate after each meal could reduce the levels of liver fat in obese or overweight women with non-alcoholic fatty liver. In addition, these patients can use aerobic training to reduce the liver enzymes and the artichoke distillate to prevent the increase of these enzymes. However, artichoke distillate consumption or moderate-intensity aerobic training could not lead to improvement of the liver fat levels in two months, without following a healthy diet regimen or other medical treatments.